A comparison of synthetic fungicide and Trichoderma spp. applications against clubroot disease on cabbage - Tarigan, Ra Siska; Hutabarat, Rina Christina; Karo, Bina br; Sembiring, Perdinanta; Napitupulu, Delima; Supardi, Supardi; Wicaksono, Rudi Cahyo; Jamaluddin, Jamaluddin; Setiawati, Wiwin; Hasyim, Ahsol (Universitas Padjadjaran, 2024)
Clubroot is one of the important diseases affecting members of the Cruciferae family. This disease is caused by soil-borne pathogen, called Plasmodiophora brassicae. The pathogen produces motile spores called zoospores. This pathogen results in a drop of cruciferous plant productivity. The objectives of this research were to identify specific Trichoderma species in three districts in Sumatra Utara and to evaluate the potency of T. harzianum (both local species from Berastagi and species developed by Indonesian Vegetable Research Institute (IVEGRI)) to control the disease and then comparing them with the application of synthetic fungicide. The research was conducted in a greenhouse of Research Installation and Application of Agricultural Technology (IP2TP), Berastagi, North Sumatera from April‒September 2018, using Completely Randomized Design (CRD) with eight treatments: C1 (control-without Trichoderma), C2 (T. harzianum IVEGRI obtained from corn substrate 2 g/polybag), C3 (T. harzianum IVEGRI obtained from rice substrate 2 g/polybag), C4 (T. harzianum IVEGRI obtained from corn substrate 4 g/polybag, C5 (T. harzianum IVEGRI obtained from rice substrate 4 g/polybag), C6 (local T. harzianum obtained from corn substrate 2 g/polybag), C7 (local T. harzianum obtained from corn substrate 4 g/polybag) and C8 (synthetic fungicide Nebijin). Each treatment contained 10 polybags of plants. These treatments were replicated four times. The results exhibited there were 3 Trichoderma species found in Berastagi: T. harzianum, T. viride and T. koningii. Also, 4 g of local T. harzianum (corn substrate) has better performance (0% disease incidence and 0% disease severity) compared to other treatments.